Novel Photopneumatic Therapy for the Treatment of Rosacea - Kim, Jun Hyung (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
BACKGROUND: Rosacea is a common skin condition, but the currently available treatments are not satisfactory. OBJECTIVE: We wanted to assess the efficacy and safety of photopneumatic therapy (PPx), which delivers pneumatic energy and broadband light (400~1,200 nm), for the treatment of erythematotelangiectatic rosacea. METHODS: Twenty two patients with erythematotelangiectatic rosacea were treated 3~5 times with PPx. Three independent dermatologists evaluated the efficacy of PPx by comparing the photographs taken before and after treatment. Patient self-assessment was also done by interviews. RESULTS: The photographic assessment by the dermatologists of the improvement showed that >50% improvement occurred in 64% (14/22) of the patients. The specific categories of improvement were as follows: poor (<25% improvement), 1 patient; fair (25~50% improvement), 7 patients; good (50~75% improvement), 11 patients; and excellent (>75% improvement), 3 patients. Based on the patients' self-assessment, 20 patients (91%) acknowledged an improvement. CONCLUSION: PPx is an effective and safe treatment option for erythematotelangiectatic rosacea.